TESTING THE EFFECTIVENESS OF THE CARHART MODEL FOUR FACTORS ON EXCESS RETURNS IN INDONESIA - Yossy Imam Candika (Universitas Airlangga, 2017)
One crucial information for investor in making their investment decision is to estimate asset-pricing level. The basic principle would be high risk, high return. This research is using Carhart model (1997): market return, size, book to market, and momentum. The goal of this research is to test and analyze the influence of Carhart Four Factor Model toward Indonesian stock' excess return. Dependent variable used in this research is stock' excess return, while independent variable used are Carhart four factor model. Population used is all non-financial firms listed in Bursa Efek Indonesia from year 2010 to 2012. Total samples are 150 firms. To test the model in this research, we firstly create ten portfolio groups by combining size-book to market and size-momentum. We use multiple regression analysis by using 10 regression analysis model based on previously built 10 portfolio combinations. Statistical test on variable excess market return toward stock return on 10 portfolio shows that there exist positive significant relationship to all models. SMB is significantly impacting portfolio return to 5 models. HML is significantly impacting portfolio return to 6 models. UMD impacting positively significant toward portfolio return on 2 models. Keywords: stock excess return, Carhart four factor model, market return, size, book to market, momentum.